Effect of Electric Shock on Morphological Traits, Yield, Yield Components and Protein Content of Three Varieties of Faba Beans (Vicia faba L.) - AL-Shamma, Laith (Iraqi Journal of Science, 2023)
To investigate the effect of electric shock (ES) on morphological variations of faba bean traits, seeds of three varieties of the crop were germinated. When radical was 2-5 mm, seedling were soaked in a 1% NaCl solution for 3h, then transferred to glass container with same solution. Wire with two polar were connected to the container solution and AC current 220 V was switched on for 3,6 and 9 minutes. Seedling then washed and planted at the field in winter 2010-2011,. Factorial Experiment was arranged in randomized Complete Block Design (RCBD) with three replicates were used. Seeds were collected first season of treatments, including the treatment comparison and then planted in the winter season of 2011-2012.The results obtained in the first season causing morphological variations in most of the traits, electric shock for 9 minutes gave less day to flowering was 81.21 days, increase number of pods/plant 23.94 pod , number of seeds / pod 4.23 seed and seeds yield was 3716.42 kg/ha. Shock for 3 minutes early the flowering of plants in the second season was 74.16 days and the number of branches / plant 13.66 Branch ,number of pods / plant 14.5 Pod and gave the highest height of the plant 76.92 and 62.12 cm for both seasons, respectively. While shock for 6 minutes gave the highest seed weight in the second season, which not differ significantly with treatment comparison was also, characterized with superiority in the percentage of protein in the first season (23.1%).The Zaina variety was earlier in flowering (77.91 and 78.87 days) for the first and second seasons respectively, also gave the highest number of pods/ plant 24.91 in the first season, and highest number of seeds/pod 3.98 and 2.83 seed for two seasons and which did not differ significantly from other varieties Aguadulce and Local respectively and exceed seeds yield in the first season was 3433.99 kg / ha. Aguadulce variety was superior in plant height for two seasons77.91 and 62.12 cm, respectively. Local variety , gave highest percentage of protein which did not differ significantly with Aguadulce variety reached to 22.26 and 22.25% respectively, and in the second season showed the highest number of branches / plant 13.5 and number of pods/ plant 14.12 Pod. The interaction between the varieties and shocking treatments were significant, as given in Aguadulce variety for 9 minutes in the first season gave the highest seeds yield was 4261.02 kg / ha, while in the second season Local variety showed the highest seeds yield was 4873 kg/ha in a period of 6 minutes shock also the interaction in the first season with 6-minute period of shock was significant only in the percentage of protein was 23.98 and 23.38% for the varieties Aguadulce and Local respectively, and protein yield of Local variety was 1110.28 kg / ha in the second season. In conclusion different varieties gave different responses to period of ES indicating that one period of ES could not be recommended for all varieties due to differences in response .